2019
DOI: 10.1111/are.14446
|View full text |Cite
|
Sign up to set email alerts
|

Partial replacement of fishmeal with Clostridium autoethanogenum single‐cell protein in the diet for juvenile black sea bream ( Acanthopagrus schlegelii )

Abstract: Clostridium autoethanogenum protein (CAP) is a single‐cell protein derived from ethanol production and may have potential to become a substitute for fishmeal in aquafeeds. A 70‐day feeding trial was conducted with black sea bream (Acanthopagrus schlegelii) (mean initial weight 6.03 ± 0.09 g) to evaluate partial replacement of fishmeal with CAP in diets. Seven isonitrogenous and isoenergetic diets were formulated with graded levels of CAP (0, 4.85, 9.70, 14.55, 19.40, 38.80 and 58.20%) to replace fishmeal. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
49
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(55 citation statements)
references
References 62 publications
5
49
1
Order By: Relevance
“…It showed that high levels of CAP substitution affected the antioxidant capacity of juvenile largemouth bass, leading to the accumulation of free radicals, which damaged liver health. Inversely, replacing fish meal with CAP in feed for juvenile black sea bream did not affect the antioxidant capacity of the liver tissue (Chen Y. et al, 2020). This conflicting result may be due to different fish and protein-processing methods used, which may have an impact on the availability and digestibility of nutrients.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…It showed that high levels of CAP substitution affected the antioxidant capacity of juvenile largemouth bass, leading to the accumulation of free radicals, which damaged liver health. Inversely, replacing fish meal with CAP in feed for juvenile black sea bream did not affect the antioxidant capacity of the liver tissue (Chen Y. et al, 2020). This conflicting result may be due to different fish and protein-processing methods used, which may have an impact on the availability and digestibility of nutrients.…”
Section: Discussionmentioning
confidence: 95%
“…However, when the level of CAP replacement fish meal exceeds 50%, it will have a negative impact on the growth performance of largemouth bass. On the one hand, the content of lysine in CAP is low, and lysine has a great influence on the growth center (Chen Y. et al, 2020;Wang et al, 2020). Therefore, the relative lack of lysine content in feeds with high CAP replacement levels may cause the growth performance of the D4 group to decline.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gas fermentation by carbon fixing chemolithoautotrophic organisms, such as Clostridium autoethanogenum , offers an opportunity to recycle carbon and harness energy from synthesis gas (syngas) generated through gasification of organic biomass (such as agricultural waste, unsorted and nonrecyclable municipal solid waste or industrial waste) or industrial off-gases. Carbon recycled by C. autoethanogenum can be applied toward the production of transportation fuels, nutritionally valuable food additives for animal feed and chemicals ( 4–6 ). After a decade of research and progressive scale-up, the technology has been commercialized with the first plant operating successfully, producing fuel-grade ethanol, since 2018; additional units are currently under construction ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…The oil content in bacteria and yeast is high and rich in unsaturated fatty acids. Chen et al [51] concluded that SCP produced by Chlostridium autoethanogenum had 88.93% crude protein and most of essential amino acids were higher than that of fish meal.…”
Section: Single-cell Proteinmentioning
confidence: 99%